Estimating lactation milk yield in Murrah buffaloes - DASS, GOPAL; SHARMA, R C (The Indian Journal of Animal Sciences, 2013)
The first lactation daily milk yield records of 404 Murrah buffaloes maintained at the NDRI, Karnal, were utilized to estimate 305 days or less milk yield by using systematic and stratified random sampling schemes with 3 test intervals (fortnightly. monthly and bimonthly). Five measures (average error, per cent average error, average absolute enor. per cent average absolute error and standard deviation of error) were used to evaluate the accuracy of both the schemes under different test-day intervals fur the estimation of 305 days or less milk yield. The accuracy of estimation decreased with increase in sampling intervals under both the schemes. The average per cent error in the prediction of 305 days or less milk yield ranged from 1 (fortnightly) to 3 (bimonthly).